Role of Large-Format Shops in the Food Retail Market in Poland during the Covid-19 Pandemic - Merło, Paweł (Olsztyn Economic Journal, 2024)
Crisis events in the past few years, including the COVID-19 pandemic, have in many cases laid bare insufficient resilience to changes in demand among businesses operating in Poland, particularly those in the service sector. Many have had to modify their way of distributing goods and to adjust to the new circumstances. As for the food retail sector in Poland, despite numerous restrictions and difficulties that consumers faced when visiting grocery shops, fluctuations in levels of food sales were relatively small. Large-format shops proved relatively adaptable, as they had already been using various distribution channels before the pandemic, and to a large extent this experience granted them quite a smooth passage through the pandemic. An important characteristic of supermarkets and hypermarkets is that their owners tend to have a large capital at their disposal, which additionally strengthens the resilience of such retail outlets to periodic crises, in contrast to smaller shops, whose financial cushion is much smaller, rendering them far more exposed to negative consequences of crises.